2023
DOI: 10.1001/jamanetworkopen.2023.0561
|View full text |Cite
|
Sign up to set email alerts
|

Association of Long-term Exposure to Particulate Air Pollution With Cardiovascular Events in California

Abstract: ImportanceLong-term exposure to fine particulate air pollution (PM2.5) is a known risk factor for cardiovascular events, but controversy remains as to whether the current National Ambient Air Quality Standard (12 μg/m3 for 1-year mean PM2.5) is sufficiently protective.ObjectiveTo evaluate the associations between long-term fine particulate air pollution and cardiovascular events using electronic health record and geocoded address data.Design, Setting, and ParticipantsThis retrospective cohort study included ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…As an alternative method to the Cox proportional hazards model, the discrete-time approach is flexible and can be used to estimate associations over the event time based on the proportional hazards assumption or obtain estimates for different time points to relax the assumption. 26,[37][38][39] In this study, we estimated associations based on the proportional hazards assumption by using the discrete-time method in our main analysis and compared the results with that of the Cox proportional hazards model in the sensitivity analysis. We examined associations with long-term heat exposure during the entire pregnancy and by trimester.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As an alternative method to the Cox proportional hazards model, the discrete-time approach is flexible and can be used to estimate associations over the event time based on the proportional hazards assumption or obtain estimates for different time points to relax the assumption. 26,[37][38][39] In this study, we estimated associations based on the proportional hazards assumption by using the discrete-time method in our main analysis and compared the results with that of the Cox proportional hazards model in the sensitivity analysis. We examined associations with long-term heat exposure during the entire pregnancy and by trimester.…”
Section: Discussionmentioning
confidence: 99%
“…We examined effect modification on the multiplicative scale of entire-pregnancy associations for the primary outcome by maternal age, race and ethnicity, education level, income level, smoking, season of conception, and green space exposure using interaction terms. 39 For the season of conception, we examined associations in the cold season (November to April) vs the warm season (May to October). For green space exposure, we examined effect modification by different levels (high [Ն50th] vs low [<50th]) of exposure to total green space, trees, low-lying vegetation, and grass in separate models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akinbami et al 48 found that children belonging to ethnoracial minority groups had as high or higher relative risk for asthma diagnoses than non-Hispanic white children, and Spiller et al 49 showed uniform RR estimates, rather than race-ethnicity specific estimates, underestimated pollution-related health impacts for minority communities. However, the literature on this topic is not consistent: Alexeeff et al 50 did not find a difference in the association between exposure to PM2.5 and COPD by race or ethnicity, and Parker et al 51 similarly found that the association between PM2.5 and heart disease mortality was not statistically different for non-Hispanic white adults versus Black or Hispanic adults. Since the literature remains inconsistent on this topic, it is unknown how race-and ethnicity-specific RR estimates would impact the findings uncovered herein.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, there has been greater recognition of the risks associated with climate change, pollutants, and the built environment, 2 and several studies have demonstrated associations with cardiovascular risk factors 3 and acute cardiovascular events. 4 However, we have lacked comprehensive tools to measure and track the dynamic nature of exposures at an individual and geographic level.…”
mentioning
confidence: 99%